The Role of Mobiles and Women in the Sustainable Local Economic Development - Karyotaki , Maria; Drigas, Athanasios; Skianis, Charalabos (International Journal of Interactive Mobile Technologies (iJIM), 2022)
Women’s access and training to use mobile technology can set the ground for creating trusted communities that provide valuable guidance on new partnerships as well as alternative business models. Such business models encompass innovative business plans adapted to the Agenda 2030 for sustainable development. Electronic commerce or small and medium-sized enterprises are pivotal to women’s entrepreneurship and they are both grounded on the adoption of mobile marketing technology and on the prolongment of the product life cycle by giving consumers’ control on its production, reuse and resale. In addition, mobile technology advancement as well as innovation, proactiveness and risk-taking initiatives can assist women to grow their business, enhance gender equality and provide long-term economic stability for a country.